Optimalisasi Keuntungan Produksi Biji Coffee Menggunakan Programan Linear Metode Simpleks - Palahudin Palahudin; Agil Maulana Achyar; Aurel Oktaviani Putri; Muhammad Ghifari Fauzan; Nazwa Riani Ahmad; Zahra Yunisa Olivia (Lokawati : Jurnal Penelitian Manajemen dan Inovasi Riset, 2025)
Optimizing the profit from coffee bean production is crucial in the coffee industry consider the competitive environment and the need for maximize revenue. The aim of this research is to use the Simplex linear programming method to determine and maximize profits from coffee bean production. This technique is used to ascertain the best combination of coffee bean production volumes while still considering a number of limitations, including scarce resources (labor, raw materials and machines) and market demand. The findings of this research show that by using the Simplex approach, companies can maximize the profit generated from coffee bean production while adhering to the existing constraints. The simulation conducted provides an optimal solution in terms of the precise production volume for each type of coffee product, contributing significantly to production planning and business strategy.